In vitro study on how photodynamic therapy and calcium hydroxide medication influence adhesive interface properties of glass-fiber posts to intraradicular dentin - Strazzi-Sahyon, Henrico Badaoui [UNESP]; Banci, Henrique Augusto [UNESP]; Melo, Fernanda Santos de [UNESP]; Soares, Lucas Silva; Spin-Neto, Rubens; Duarte, Marco Antonio Hungaro; Cintra, Luciano Tavares Angelo [UNESP]; Santos, Paulo Henrique dos [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Elsevier, 2023)
Purpose: This in vitro study evaluated the influence of antimicrobial photodynamic therapy (aPDT), using methylene blue (MB) as photosensitizer (PS) and calcium hydroxide (CH) as intracanal medication on adhesive bond strength, sealing, and integrity of the luting interface of glass-fiber posts to different thirds of endodontically treated root canal dentin. Material and methods: 102 incisors were sorted into 6 groups: a negative control irrigated with deionized water; a positive control irrigated with deionized water and filled with CH; CH + MB 50 mg/L without laser radiation; CH + MB 100 mg/L without laser radiation; CH + MB 50 mg/L radiated by red laser; and CH + MB 100 mg/L radiated by red laser. Push-out bond strength (n = 8), adhesive interface sealing (n = 3), and volume and quantification of voids (n = 6) were assessed using a universal testing machine, confocal laser scanning microscope, and computerized microtomography, respectively. Scanning electron micrographs were obtained from representative samples to qualify the fracture patterns. Push-out bond strength and adhesive interface integrity data were subjected to 2-way ANOVA for repeated measures followed by Tukey's test (α = 0.05). Adhesive interface sealing was evaluated by the inter-examiner Kappa test and submitted to Kruskal-Wallis and Dunns tests (α = 0.05). Results: Assessing the apical region, the positive control and MB100WA + Ca(OH)2 groups showed lower adhesive bond strength compared to the MB100A + Ca(OH)2 group (P < 0.05). The cervical third showed higher bond strength than the apical third for the positive control, MB50WA + Ca(OH)2, MB100WA + Ca(OH)2, and MB50A + Ca(OH)2 groups (P < 0.05). A prevalence of mixed failure was observed in all experimental groups. There were no statistically significant differences in adhesive interface sealing for any of the parameters assessed (P > 0.05). MB100WA + Ca(OH)2 and MB100A + Ca(OH)2 groups promoted a higher volume and quantification of voids compared to the negative control group evaluating the cervical third (P < 0.05). In general, there were no differences in the quantification of voids comparing the intraradicular thirds (P > 0.05), differently to the volume of voids in which, in general, the cervical third promoted higher values compared to the middle and apical thirds (P < 0.05). Conclusion: aPDT with methylene blue PS at 50 mg/L associated with calcium hydroxide as intracanal medication demonstrated satisfactory bond strength, sealing, and integrity of the adhesive interface at any intraradicular depth.
Photodynamic therapy on adhesive interface of glass-fiber posts
Keywords: Bond strength; Calcium hydroxide; Dentin; Methylene blue; Photodynamic therapy; Resin cements